Performance Analysis of Multiantenna MC DS CDMA System Over Correlated Î·âÂµ Multipath Fading Channels - Amok, J.O.M. (Springer New York LLC, 2016)
In wireless communication channels, the performance of the wireless communication systems deteriorate due to the severe influence of interference, multipath fading, path loss, shadowing, and noise, respectively. In this paper, we investigate the performance of the system transmitting over correlated Î·âÂµ frequency selective fading channels in terms of average error rates. Based on moment generating function approach, closed form expressions for average error probabilities for the system are derived and represented in terms of Appellâs hypergeometric functions and Lauricellaâs multivariate hypergeometric functions. In addition, probability density function based approach is employed to determine the formulae for average error probabilities of the system operating over correlated Î·âÂµ multipath fading channels. The numerical results reveal that, the effects of correlation, decaying power factor and signal constellation size can be reduced using frequency, spatial antennas and path diversities, respectively. Furthermore, we confirm the correctness of the analytical approaches through Monte Carlo simulation technique. Â© 2016, Springer Science+Business Media New York.